Identifikasi Kriteria Pekerja Informal terhadap Pemilik Usaha Makan Minum di Jakarta - A.D. Hendro; D. Khiat; R. S. Wibisono; R. Nike; R. Mahendradani (Universitas Prasetiya Mulya, 2021)
More than 55 percent of Indonesian workers consist of informal workers. This includes the Food & Beverage (F&B) sector as well. Most of the job in F&B industry did not require high skill and experience due to the job replaceability nature. This led to lack of employment security, regulation, and social safety net. Most of them are paid in day to day basis with low job security. This factor leads to high workforce turnover rate. In the other hand, the Informal Small-Medium Enterprises (SME) owner in F&B sector did not have enough resource to hire formal workers. Because formal workers must have social security, and several other benefits that the business owner has to provide. Therefore, there are high demands for informal workers to satisfy their needs. This paper written know what criteria that the informal SME owner in F&B sector in Jakarta consider of hiring to support their business.